Modelling of Bidirectional DC-DC Converter with DualBattery Energy Storage: An Application for Hybrid Electric Vehicle System - G. Pavani, Ch. Sathish, P. Saritha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study develops a newly designed, patented, bidirectional dc/dc converter (BDC) that interfaces a main energy storage (ES1), an auxiliary energy storage (ES2), and dc-bus of different voltage levels, for application in hybrid electric vehicle systems. The proposed converter can operate in a step-up mode (i.e., low-voltage dual-source-powering mode) and a step-down (i.e., high-voltage dc-link energy-regenerating mode), both with bidirectional power flow control. In addition, the model can independently control power flow between any two low-voltage sources (i.e., low-voltage dual-source buck/boost mode). Herein, the circuit configuration, operation, steady-state analysis, and closed-loop control of the proposed BDC are discussed according to its three modes of power transfer. Moreover, the simulation and experimental results for a 1 kW prototype system are provided to validate the proposed converter